Effects of Extreme Drought and Water Scarcity on Consumer Behaviour: The Impact of Water Consumption Awareness and Consumers’ Choices - Veloso, Sofia de Sousa (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Driven Marketing, specialization in Marketing Intelligence